Study on the Performance of Expansive Subgrade Soil Stabilized with Enset Ash - Derara Neguse; Eleyas Assefa; S. M. Assefa (Advances in Civil Engineering)
This paper deals with the effect of Enset ash on the mechanical property of expansive soil used as a subgrade material in road construction works. To investigate the influence of Enset ash on the behavior of expansive soils, laboratory tests were conducted according to AASHTO, ASTM, IS, and BS standards. The laboratory results show that the expansive soil belongs to the A-7-5 class of soil in AASHTO and CH class in the USCS. The liquid limit, plasticity index, free swell index, and free swell ratio of the soil have decreased with the increasing content of Enset ash. The strength test result shows CBR and UCS, and OMC increases and decreases in MDD value with increasing content of Enset ash. The microstructural properties of natural soil and stabilized soil were selected based on strength properties and were observed by a scanning electron microscopy (SEM) imaging device, and the result clearly shows the alteration in the fabric and morphology of the natural soil. The mineralogical composition of expansive soil is identified by XRD, and the result shows that the expansive soil in the study area is mainly composed of quartz and montmorillonite, which separately take up 50% and 38.5% of the total air-dried sample, while the percentage of kaolinite was 11.5%. From this study, it has been found that Enset ash stabilized soil that satisfies the minimum requirement of the Ethiopian Road Authority pavement manual specification for use as a subgrade material in road construction works.